Acute Kidney Injury in Elderly Patients With Coronavirus Infectious Disease: A Study of Incidence, Risk Factors, and Prognosis in Brazil - Yuasa, Bruna Kaori; Magalhães, Luis Eduardo; Oliveira, Paula Gabriela Sousa de; Yokota, Lais Gabriela; Cardoso, Pedro Andriolo; Zamoner, Welder; Balbi, André Luis; Ponce, Daniela (Frontiers in Nephrology, 2022)
Introduction: Elderly patients with COVID-19 are at a higher risk of severity and death as not only several comorbidities but also aging itself has been considered a relevant risk factor. Acute kidney injury (AKI), one of the worst complications of SARS-CoV-2 infection, is associated with worse outcomes. Studies on AKI with COVID-19 in Latin-American patients of older age remain scarce. Objectives: To determine AKI incidence and the risk factors associated with its development, as well as to compare outcome of elderly patients with or without AKI associated with SARS-CoV-2 infection Methods: This retrospective cohort study evaluated patients with SARS-CoV2 infection admitted to a Public Tertiary Referral Hospital from 03/01/2020 to 12/31/2020, from admission to resolution (hospital discharge or death). Demographic, clinical, and laboratory data were collected from patients during hospitalization. Daily kidney function assessment was performed by measuring serum creatinine and urine output. AKI was diagnosed according to KDIGO 2012 criteria. Results: Of the 347 patients with COVID-19 admitted to our hospital during the study period, 52.16% were elderly, with a median age of 72 years (65- 80 years). In this age group, most patients were males (56.91%), hypertensive (73.48%), and required ICU care (55.25%). AKI overall incidence in the elderly was 56.9%, with higher frequency in ICU patients (p < 0.001). There was a predominance of KDIGO 3 (50.48%), and acute kidney replacement therapy (AKRT) was required by 47.57% of the patients. The risk factors associated with AKI development were higher baseline creatinine level (OR 10.54, CI 1.22 -90.61, p = 0.032) and need for mechanical ventilation (OR 9.26, CI 1.08-79.26, p = 0.042). Mortality was also more frequent among patients with AKI (46.41%vs24.7%, p < 0.0001), with death being associated with CPK level (OR 1.009, CI 1.001-1.017, p = 0.042), need for mechanical ventilation (OR 17.71, CI 1.13-277.62, p = 0.002) and KDIGO 3 (OR 2.017 CI 1.039 -3.917, p = 0.038) Conclusion: AKI was frequent among the elderly hospitalized with COVID-19 and its risk factors were higher baseline creatinine and need for mechanical ventilation. AKI was independently associated with a higher risk of death.